PSYCHOLOGICAL MONITORING OF UNIVERSALISTIC EDUCATIONAL ACTIVITY AND LEARNING OUTCOMES - A. Y. Kachimskaya (Acta Biomedica Scientifica)
The article discusses the selection criteria and specific techniques for assessing cognitive, personal, regulatory and uni-versalistic communicative activities of primary school students. It describes the experience of psychological monitoring of universalistic education activities within the operation of Basic Department of Practical Psychology in Education. Arguments are given of using valid psychodiagnostic methods for assessing cognitive maturity of regulatory, communication and personal universalistic education activities. The article presents the option of using psycho-diagnostic tools to assess the level of formation of universalistic educational activity in schoolchildren. The paper describes the author's method of assessing regulatory and universalistic communicative activities of pupils. The author presents a method of estimating the educational results of the students, which provides a reliable psychological and pedagogical material.